Risk factors associated with carotid intima-media thickness in pediatric nephrotic syndrome - Khairunnisa Khairunnisa; Syafruddin Haris; Isra Firmansyah; Anidar Anidar; Mulya Safri; Herlina Dimiati (AcTion: Aceh Nutrition Journal, 2024)
Nephrotic syndrome (NS) is the most frequently occurring kidney disease among children and increases the morbidity and mortality of cardiovascular disorders caused by hyperlipidemia, increased thrombogenesis, and endothelial dysfunction that occur in atherosclerosis. Carotid intima-media thickness (CIMT) is an accessible, noninvasive, and sensitive method for detecting subclinical atherosclerosis. This study aimed to determine the risk factors for CIMT in children with idiopathic nephrotic syndrome at RSUD dr. Zainoel Abidin Banda Aceh. This was an observational analytic study with a cross-sectional design, conducted from March 2024 until May 2024. This study included 35 patients with NS who were 2-18 years, receiving treatment for a minimum of 6 months, with a glomerular filtration rate exceeding 90 ml/minute/1,73 m2, and no recent acute infections in the past 3 months. Bivariate analysis was performed using the Pearson correlation test, and independent T tests and multivariate analyses were performed using multiple linear regressions. We found a statistically significant correlation between CIMT and total cholesterol (p=0,004, r=0,471), steroid-resistant nephrotic syndrome (p=0,001) and systolic blood pressure (p=0,011, r=0,427) with a mean CIMT of 1,5 ± 0,4 mm. In conclusion, the total cholesterol level, steroid-resistant nephrotic syndrome, and systolic blood pressure are risk factors for CIMT in children with NS.